Design of an Android Based Garbage Transport (Angkut's) Application - Muhamad Alda; Tamaulina Barus; M. Farhan Alyuda; Novtra Refiardiansyah Nasution; Muhammad Ridho Nasution (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
The waste problem in urban areas, such as Belawan, Medan, is exacerbated by population growth and inadequate waste management systems, resulting in environmental degradation. To address this issue, "Angkut's," an Android-based waste transportation application, has been developed. The system aims to optimize waste management through the use of digital technology, allowing users to schedule and monitor waste collection efficiently. This application addresses inefficiencies in the existing waste transportation system by incorporating features like real-time order tracking and notifications for both users and administrators. The prototype for Angkut's was developed using prototyping methodology, which includes stages such as communication, quick planning, quick design modeling, prototype construction, and deployment feedback. The application includes various user-friendly interfaces, such as a splash screen, login, home, and order management pages. Administrators can monitor order statuses and provide updates on waste collection. The system also promotes community empowerment in waste management by using a structured approach to managing inorganic waste. After development, the prototype underwent testing to evaluate user responses and functionality. This application is expected to improve waste transportation efficiency, benefiting both the community and local governments.